Animate Metaphors to Satire Leaders in Tenas Effendy's Pantun "Kelakar" - Essy Syam; Qori Islami Aris; Vita Amelia (Anaphora : Journal of Language, Literary, and Cultural Studies, 2022)
This writing deals with an analysis of Pantun Kelakar written by Tenas Effendy by focusing on 4 ( four) of them and analysis the animate metaphors ( animal metaphors) used in these four pantuns in exploring how those animate metaphors reflects leaders’ characters. This study is descriptive analysis where this study aims to describe the existing phenomena. In this case, this study describes the animate metaphors in Pantun Kelakar of Tenas effendy which satire leaders. The animal metaphors found in those 4 pantuns are; crocodile, monkey, lion and snake, and those animals are the analogy of leaders whose characters are associated with the characters of the animals in which they are associated with. Crocodile is the metaphor to satire leader who ignore the rules in taking or consuming something which leads to the life without guidance. The monkey is the metaphor to satire a leader who does immoral deeds. A lion is used as the metaphor of powerful leader who destroys his/her people and snake is the metaphor of sly or cunning leader. by describing those metaphors, this analysis may contribute to create awareness for leaders whose characters are reflected by the metaphors to treat this analysis as a self-reminder to change and improve the person’s character. and in the same time, this analysis may also contribute to give knowledge about some kinds of leaders with their specific characters in leading their people